Pengaruh Temperatur Austenit dengan Holding Time 2 Jam Terhadap Kekerasan dan Ketangguhan Baja ST 42 - Nitha; Yafet Bontong; Petrus Sampelawang; Lantana Dioren Rumpa; Nofrianto Pasae; Fikran (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2024)
Steel is an alloy metal with iron as the basic element and carbon as the main alloying element. The carbon content in steel ranges from 0.2% to 2.1% by weight according to the grade. The function of carbon in steel is as a hardening element. This research aims to determine the effect of austenite temperature with a holding time of 2 hours on the hardness and toughness of ST 42 steel. The material for this research is ST 42 steel. This research was carried out experimentally using the Vickers method and impact method, with temperature variations of 950℃, 960℃, 970℃, 980℃. From the results of the hardness research, it can be concluded that the higher the austenite temperature variation with a holding time of 2 hours, the higher the hardness value in ST 42 steel, where the highest value at a temperature of 980℃ is 204.8 kg/mm2, and the lowest is in a normal specimen with a value of 186.6 kg/mm2, and from the toughness research results it can be concluded that the higher the austenite temperature variation with a holding time of 2 hours, the lower the toughness value of ST 42 steel, where the highest value at an austenite temperature of 960°C is 2,023 Joules/mm2 and the lowest in normal specimens it is 0.866 Joules/mm2.